Women and urban informal sector - Mishra, Shashi A. (New Delhi : Discovery Pub. House, 2010)
Study conducted in Mumbai, India.
Includes index.
Includes bibliographical references.
Keywords: Women -- Employment -- India -- Mumbai; Informal sector (Economics) -- India -- Mumbai; Women employees -- Government policy -- India -- Mumbai